2011
DOI: 10.1097/pcc.0b013e31820aba5b
|View full text |Cite
|
Sign up to set email alerts
|

Withholding or withdrawing life-sustaining treatments: An 8-yr retrospective review in a Spanish pediatric intensive care unit

Abstract: Withholding or withdrawing life-sustaining treatment was a frequent mode of death in our pediatric intensive care unit, occurring at a rate that falls in the midrange of literature values. The level of the parents' involvement with the team in the decision-making process, which was documented in 88 of 97 of the medical charts, was very high. Patients with chronic neurologic diseases or with severe cognitive sequelae constituted the main group in which the decision to forgo life-sustaining treatment was made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 8 publications
5
22
2
1
Order By: Relevance
“…This confirms a substantial burden of newly diagnosed neurologic injuries even in patients who die during the course of CICU admission. In contrast to previous studies in a general pediatric intensive care setting, we could not find an association between neurologic injury and foregoing life-sustaining treatment in our CICU (p = 0.23) (17,18).…”
Section: Discussioncontrasting
confidence: 85%
“…This confirms a substantial burden of newly diagnosed neurologic injuries even in patients who die during the course of CICU admission. In contrast to previous studies in a general pediatric intensive care setting, we could not find an association between neurologic injury and foregoing life-sustaining treatment in our CICU (p = 0.23) (17,18).…”
Section: Discussioncontrasting
confidence: 85%
“…According to literature, the religious background19 34 and the length of professional experience of clinicians may be important impact factors;9 14 however, in our research, no differences were found in attitude score among different religious beliefs and professional backgrounds. The reason for the differences between this research and previous literature may be that demographic data in these research participants presented a centralised tendency, such as a predominance of Buddhism or Taoism (table 1).…”
Section: Discussioncontrasting
confidence: 61%
“…This may be one reason that a previous study found that dying neonates received insufficient analgesic medicines in NICUs in Taiwan 4. To compare results with other studies conducted in Spain,19 USA,20 Italy, France, The Netherlands and Sweden,6 research participants were more likely to express concern regarding the use of analgesics in NICUs. This research result showed that there is an urgent need to change and improve the neonatal professionals' attitudes regarding pain control care for these terminally ill neonates in Taiwan.…”
Section: Discussionmentioning
confidence: 94%
“…In developed countries, most pediatric deaths occur in intensive care settings (13). Severely ill children are admitted to pediatric intensive care units (PICUs) to receive potentially curative therapies.…”
Section: Introductionmentioning
confidence: 99%